An Assessment of Performance in the Routine Analysis of Silicate Rocks Based on an Analysis of Data Submitted to the GeoPT Proficiency Testing Programme for Geochemical Laboratories (2001–2011). Issue 4 (20th May 2013) - Potts, Philip J.; Webb, Peter C.; Thompson, Michael
<x xml:space="preserve">Abstract</x> Data reported by laboratories contributing to the GeoPT proficiency testing programme for geochemical laboratories over the period from 2001 to 2011 have been assessed to identify the elements and concentration ranges over which analytical performance can be considered satisfactory. Criteria developed in the paper indicated that performance in the content determination of the elements/constituents SiO2, Al2O3, MnO, Cs, Dy, Er, Eu, Ga, Hf, Ho, Lu, Nd, Pr, Sm, Sr, Tb, Tl, Tm, U, Y, Yb and Zn was satisfactory over the full concentration range assessed. The elements/constituents TiO2, Fe2O3(T), MgO, CaO, Na2O, K2O, P2O5, Ba, Be, Cd, Ce, Co, Gd, La, Li, Nb, Rb, Sb, Sc, Sn, Ta, Th, V and Zr showed some degradation in performance at lower concentration levels (approaching the detection limit of some techniques). Performance in determining LOI, As, Bi, Cr, Cu, Ge, Mo, Ni, Pb and W was in general unsatisfactory over the full concentration range assessed. Other elements (especially Fe(II)O, H2O+, CO2, Ag, Au, B, Br, Cl, F, Hg, I, In, Ir, N, Os, Pd, Pt, Re, Rh, S, Se, Te) could not be evaluated as they were not routinely reported by laboratories participating in the GeoPT programme, often because they are present in silicate rocks at sufficiently low concentrations to require a pre‐concentration stage. Some suggestions are made for the causes of unsatisfactory performance, but further progress will require a detailed assessment of the methods used by participating laboratories, which will form the subject of a further paper.